Assessing the Vocational Taxonomy Hierarchy - Sadrina; Ramlee Mustapha; Norhazizi Bin Lebai Long; Yuyun Yuana (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
English:Taxonomy recently defined as the naming or classification of an idea or name, in terms of one discipline. However, there is a lack of regulation in the concept of vocational education. Based on Bloom, the taxonomy is built to determine the level of cognitive, affective, and psychomotor ability. Higher Vocational education (SMK) cannot fully use Bloom's Taxonomy. Vocational Taxonomy is dependent on the psychomotor theory which emphasizes aspects of physical movement. However, the purpose of this research is to determine the Vocational Taxonomy hierarchical structure for SMK N 1 Jeunib. The design of this research is a qualitative research which using the interview method to assess the perception of the Vocational teacher in terms of determining the Vocational Taxonomy. The sample chosen was SMKN 1 Jeunib, Bireun, Aceh, which selected 54 teachers from all departments. From the data, the respondents presented that they believed the Vocational Taxonomy is important in terms of learning and teaching. Then, the taxonomic function is very important and assisting in teaching and learning, aiding the curriculum preparation, and contributing the practical activities. However, the taxonomy function is important in the measurement and assessment of psychomotor activities. It was recommended that Vocational Taxonomy was important to apply. The research also stated that there was a need for a link between cognitive and psychomotor aspects. Bahasa: Taksonomi diartikan sebagai penamaan atau klasifikasi suatu gagasan atau nama, dalam satu disiplin ilmu. Berdasarkan Bloom, taksonomi dibangun untuk mengetahui tingkat kemampuan kognitif, afektif, dan psikomotorik. Pendidikan Tinggi Kejuruan (SMK) tidak dapat sepenuhnya menggunakan Taksonomi Bloom. Taksonomi Vokasi bergantung pada teori psikomotorik yang menekankan pada aspek gerak fisik. Adapun, tujuan dari penelitian ini adalah untuk mengetahui struktur hierarki Taksonomi Kejuruan SMK N 1 Jeunib. Desain penelitian ini adalah penelitian kuantitatif dengan metode survey untuk menilai persepsi guru SMK dalam menentukan Taksonomi SMK. Sampel yang dipilih adalah SMKN 1 Jeunib, Bireun, Aceh yang memilih 54 guru dari semua jurusan. Dari data tersebut, responden menyatakan bahwa mereka percaya Taksonomi Kejuruan penting dalam hal belajar dan mengajar. Kemudian, fungsi taksonomi sangat penting dan membantu dalam proses belajar mengajar, membantu penyusunan kurikulum, dan menyumbangkan kegiatan praktis. Fungsi taksonomi penting dalam pengukuran dan penilaian aktivitas psikomotorik. Direkomendasikan bahwa Taksonomi Kejuruan penting untuk diterapkan. Penelitian tersebut juga menyatakan bahwa perlu adanya keterkaitan antara aspek kognitif dan psikomotorik.